2011
DOI: 10.1002/jor.21420
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate patch prevents steroid‐related bone necrosis

Abstract: Avascular necrosis of the femoral head is a common complication with disabling effect for young patients after high-dose corticosteroid treatment. We could show that steroids have a vasoconstrictive effect on lateral epiphyseal arteries of the femoral head which could lead to ischemia and subsequent necrosis. In this study we investigated the preventive effect of a nitrate patch on steroidrelated bone necrosis in a rabbit model. New Zealand White rabbits (male; 3-4.5 kg bodyweight) were injected with 20 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Notably, promoted adipogenic differentiation led to disordered osteogenic differentiation, and the accumulation of adipocytes might lead to a high intramedullary pressure and impair brittle blood circulation in the femoral heads . Moreover, fat emboli in vessels and sinusoids can also indirectly induce intravascular coagulation via the complement signalling pathways and deposition of immune complex, whereas antithrombotic reagents have protective effects to promote circulation and ameliorate ONFH . In this work, we found that ethanol could stimulate BMSCs towards adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 73%
“…Notably, promoted adipogenic differentiation led to disordered osteogenic differentiation, and the accumulation of adipocytes might lead to a high intramedullary pressure and impair brittle blood circulation in the femoral heads . Moreover, fat emboli in vessels and sinusoids can also indirectly induce intravascular coagulation via the complement signalling pathways and deposition of immune complex, whereas antithrombotic reagents have protective effects to promote circulation and ameliorate ONFH . In this work, we found that ethanol could stimulate BMSCs towards adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 73%
“…the interest in finding appropriate treatments for precollapse disease 67,72,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146] . Treating asymptomatic osteonecrosis of the hip is controversial, with 59% of such hips becoming symptomatic in three years, and 7% of small and 80% of large lesions (a Kerboul angle of >240°) collapsing by eight years.…”
Section: Nonoperative Therapymentioning
confidence: 99%
“…Previous studies have tried to prevent the generation of steroid-induced femoral head osteonecrosis (SANFH), for example, enoxaparin and nitrate patch could use to prevent the occurrence of SANFH (16,17), while the potential mechanism was not fully understand. Liu et al found that miR-206 regulated connexin43 that involved in the osteogenic differentiation in SANFH (13).…”
Section: Discussionmentioning
confidence: 99%